Impact of energy storage strategies on gametogenesis and reproductive effort in diploid and triploid Pacific oysters Crassostrea gigas — Involvement of insulin signaling - Jouaux, A.; Blin, J.L.; Adeline, B.; Heude-Berthelin, C.; Sourdaine, P.; Mathieu, M.; Kellner, K. (Aquaculture, 2013)
International audience Gametogenesis of the Pacific oyster Crassostrea gigas follows an annual cycle. In this work, we used contrasting dietary conditions (fed and unfed) for a preconditioning treatment in order to impact glycogen storage supporting reproductive pathways in diploid and triploid animals before a broodstock conditioning treatment. In diploid oysters, food deprivation during preconditioning led to reduced gonia proliferation as demonstrated by lower PCNA (Proliferating Cell Nuclear Antigen) expression and subsequently, the reproductive effort was significantly reduced. For triploid animals exhibiting arrested gametogenesis, dietary conditions impacted the ratio of α (animals with unlocked gametogenesis) and β (animals with locked gametogenesis). Thermal stress applied to these conditioned animals confirmed the weakness of diploid animals with high stored reserves and intense reproductive effort, versus low reproductive effort. Moreover, only low mortalities were observed for triploid animals whatever the reproductive status. The involvement of the insulin pathway in the regulation of gametogenesis and storage rebuilding was assessed by measuring an increased expression of CIR (C. gigas insulin related receptor) in unfed oysters.